Economic justification of the use of bicomponent beverages based on pectin substances on the example of vegetable juices - Donchenko Lyudmila V.; Belousova Anna I. (E3S Web of Conferences, 2021)
Modern food technologies are not able to preserve the healthy components of original natural raw materials in finished products. The example is the production of industrial juices. It is known that freshly squeezed juices quickly deteriorate. In order to preserve their vitamins, useful components and increase the shelf life, water is immediately removed from freshly squeezed juices in a vacuum at a temperature of 30°C. It is known that water is not only an environment favorable for the bacteria reproduction, but also a strong chemical reagent that easily decomposes all the useful components contained in food. In addition, chemical interactions occur in the water, that is, decomposition reactions, and they can only be stopped by removing water from the food system. When sterilized by heating, the chemical processes of decomposition of healthy aromatic components are accelerated. As a result, the nutritional value of such drinks is reduced. The main trend in food market is the expansion of range and volume of production of functional beverages containing the necessary nutrients.